In‐Plane Uniaxial Helical‐Axis Alignment in Chiral‐Nematic Liquid Crystal Polymer Films Using Photogradient Polymerization - Yuki Shikata; Shohei Sugiyama; Kohsuke Matsumoto; Kyohei Hisano; Osamu Tsutsumi (Small Structures)
Chiral‐nematic liquid‐crystal (N* LC) polymer films with uniaxially controlled helical‐axis alignments have attracted increasing attention for developing next‐generation materials with promising mechanical, optical, and electronic properties. These functionalities in N* LC polymer films can be realized by controlling their helical‐axis alignment. However, achieving precise control over helical‐axis alignment in polymer films remains challenging. This study presents a simple and effective method for controlling uniaxial helical‐axis alignment in polymer films through photogradient polymerization. This approach induces a direction‐controlled isotropic‐to‐N* LC phase transition driven by a polymer concentration gradient, resulting in uniaxial helical‐axis alignment along the phase transition direction. The proposed method offers valuable insights for the facile fabrication of N* LC polymer films with controlled helical‐axis alignments.